Strengthening Teacher Professionalism in the Digital Learning Era: Perspectives on Continuous Competency Development, Career Advancement, and Professional Reflection - Faqih Mufasirin; Tsania Nelly Fakhrina; Ninda Febriyanti; Ma'mun Hanif (Jurnal Ilmiah Profesi Pendidikan, 2026)
The rapid development of digital technology has transformed educational practices and increased the demands on teacher professionalism. This study aims to analyze strategies for strengthening teacher professionalism in the digital era. The study employed a library research method by reviewing relevant books, scholarly articles, and previous studies, while the collected data were analyzed using content analysis. The findings indicate that strengthening teacher professionalism requires the development of digital competencies, continuous professional development, lifelong learning, and regular self-reflection and professional evaluation. Furthermore, institutional support through training programs, professional learning communities, academic supervision, and supportive educational policies plays a significant role in enhancing teachers' professional capacity. In conclusion, strengthening teacher professionalism in the digital era requires the integration of individual commitment and institutional support to enable teachers to effectively respond to technological changes and improve the quality of teaching and learning.